A phytochemical study of Stemodia maritima L. - Guerrero, Ricardo Oswaldo
Preliminary studies of extracts of Stemodia maritima L. at the Department of Pharmacognosy, School of Pharmacy, University of Mississippi, showed antibacterial activity. The above ground plant material was extracted and fractionated. Column chromatographic procedures resulted in the isolation and characterization of four known compounds: the diterpenes, stemodin and stemodinone; a sugar alcohol, D-mannitol; and a flavonol, rhamnazin. Four new constituents were also isolated, the diterpenes stemodinol and maritimol, and the diterpenoid glycosides, stemodinosides A and B. The chemical structures of stemodinol and maritimol were fully characterized. The chemical structures of stemodinosides A and B were partially elucidated. Stemodinoside A was found to possess antimicrobial activity against Staphylococcus aureus and Mycobacterium smegmatis in the range of 100 ug./ml. as the minimum inhibitory concentration.
Available to the general public.
Thesis (Doctor of Philosophy in Pharmacy)--University of Mississippi, December 1974.
Keywords: Scrophulariaceae; Plants -- Analysis